NEXUS OF RISK AND STABILITY IN ISLAMIC BANKS DURING THE PANDEMIC: EVIDENCE FROM INDONESIA - Sunarsih Sunarsih; Rizqi Umar Al Hashfi; U’um Munawaroh; Endang Suhari (Journal of Islamic Monetary Economics and Finance, 2022)
This paper analyzes the effect of liquidity risk and credit risk on Islamic bank stability and whether the risk-stability nexus changes during the Covid-19 pandemic. Using a panel quarterly dataset of 14 Islamic banks from 2017 to 2020, a total of 224 quarterly-bank observations in total and the system generalized method of moment, we find that credit risk and liquidity risk are negatively associated with bank stability. Moreover, the COVID-19 does not alter the negative relationship between liquidity risk and stability. To validate the results, we also estimate the model using the LSDVC. The LSDVC results remain consistent. These results provide new insight into understanding risk management implementation for minimizing these risks.